KAJIAN KELAYAKAN SISTEM PENTANAHAN PADA TRAVO AUXILIARY CONTROL BUILDING PADA PEMBANGKIT LISTRIK TENAGA AIR (PLTA) SINGKARAK - Yan Putra, Dodi; Asrul, Junaidi; Firmansyah, Firmansyah; Roswaldi, Roswaldi; Julsam, Julsam (ITP Press, 2023)
The grounding system at the Singkarak Hydroelectric Power Plant (PLTA) uses the Grid Grounding system. In this study, we re-checked the grounding value at the Travo Auxilary Building control PLTA Singkarang, where the existing results during commissioning during the initial installation of the Travo Auxilary grounding system obtained a value of 1.22 Ohm. While the results of measurements again to carry out the feasibility of the grounding value on the Auxilary building control transformer are obtained the average value of measurements carried out with the ear tester brand Koriyutsu 4106 with a variable auxiliary electrode distance of 5 meters, 10 meters obtained a grounding value on tarvo 1 Auxilary Building 1 of 1.2 Ohm and also on transformer 2 Auxilary building control obtained a grounding value of 1.2 Ohm while the calculation results obtained a grounding value by calculating the Grid method obtained a grounding value of 0.26 Ohm. So from the results of measurements and calculations, a difference of 0.94 Ohm is obtained. From the measurement results and also the calculations, the grounding of the auxiliary building control transformer is still in very proper condition according to SPLN T5.012. year 2020 and PUIL 2011.